“Act Like my Friend”: Mothers’ Recommendations to Improve Relationships with Their Canadian Child Welfare Workers - Hughes, Judy; Chau, Shirley; Rocke, Cathy (Canadian Social Work Review / Revue canadienne de service social)

(untitled) (Canadian Association for Social Work Education / Association canadienne pour la formation en travail social (CASWE-ACFTS), 2016)
Through a final qualitative interview question, we asked mothers who were involved with the Canadian child welfare system to provide recommendations to improve practices in this system. Through their responses, these women focused on the relationships between parents and workers. Surprisingly, they stated that child welfare workers should “act like friends.” In these descriptions, they stated that child welfare workers should be respectful, honest, caring, supportive, non-judgmental, and encouraging. They further stated that workers should have empathy and provide concrete supports so that parents maintain connections to their children. First, we present the mothers’ recommendations. Then, we situate these findings into best practice literature and discuss both the possibilities and challenges of developing stronger relationships between parents and child welfare workers.